Accumulation of Disadvantages Across Multiple Domains Amongst Subgroups of Children of Parents With Schizophrenia or Bipolar Disorder: Clustering Data from the Danish High Risk and Resilience Study VIA 7. Issue 1 (27th January 2022) - Krantz, Mette Falkenberg; Ellersgaard, Ditte; Andersen, Klaus Kaae; Hemager, Nicoline; Christiani, Camilla; Spang, Katrine Søborg; Burton, Birgitte Klee; Gregersen, Maja; Søndergaard, Anne; Greve, Aja; Gantriis, Ditte Lou; Ohland, Jessica; et al.
Abstract: Objective: Children with familial high-risk of schizophrenia (FHR-SZ) or bipolar disorder (FHR-BP) are frequently affected in a range of domains known to be precursors of severe mental illness. No previous studies have gathered known precursors to examine whether they distribute evenly across familial high risk (FHR) children or if they cluster among a smaller group. Since such examination holds the potential to identify high and low risk of severe mental illness groups, we aimed to cluster FHR and control children affected to various degrees. Method: In The Danish High Risk and Resilience Study VIA 7, a clinical cohort study, 514 7-year-old children with FHR-SZ or FHR-BP and matched controls were assessed in domains of motor function, neurocognition, emotional control, behavior, social cognition, self-perception, language, psychotic experiences, and psychopathology, and grouped using cluster analysis. Associations between clusters and parents' level of education, functioning, caregiver status, child's level of stimulation and support in the home, and polygenic risk scores were examined. Results: A total of four groups including one of broadly affected children were identified. The broadly affected group was represented 4–5-fold (18.1%) amongst FHR-SZ children and 2–3-fold (10.2%) amongst FHR-BP children, compared to controls (4.1%) ( P < .001), and the broadly affected group had lower levels of caregiver functioning ( P < .001) and stimulation and support at home ( P < .001). Conclusion: Precursors of severe mental illness distribute unevenly among FHR children; while approximately half are not affected in any domains, the other half are affected to various degrees. Targeted support towards the affected groups is indicated.